Nuevos ensayos sobre el entendimiento humano - Leibniz, Gottfried Wilhelm, Freiherr von, 1646-1716 (Akal bolsillo, 2017)
Leibniz argues chapter by chapter with John Locke's Essay Concerning Human Understanding, challenging his views about knowledge, personal identity, God, morality, mind and matter, nature versus nurture, logic and language, and a host of other topics.